Food and Feeding Habit of Clarias gariepinus, Mormyrus rume rume and Synodondis budgetti in Dadin Kowa Reservoir, Gombe State, Nigeria. - S.K, Hassan,; A, Ja’afaru,; K.A, Abubakar; S, Nazeef,; M, Kabiru, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The study of food and feeding habits of Clarias gariepinus, Mormyrus rume rume and Synodondis budgetti in Dadin Kowa Reservoir were carried out for a period of Eighteen month, (October 2022 to March 2024). A total of 189 Clarias gariepinus, 81 Mormyrus rume rume and 272 Synodontis budgetti were purchased from the local fishermen as soon as they returned from their catch and were brought immediately to the laboratory for analysis. The fishes were identified using appropriate fish identification keys. Stomach contents were observed under the microscope and analysed using Frequency of occurrence, Numerical methods and Fullness method. In Clarias gariepinus, Macrophyte accounted for 23.88% and 25.96% under frequency of occurrence and numerical method followed by Insect part with 13.68% and 13.14%, Small fish, Mud, Detritus and Zooplankton had 11.67% and 10.89%; 9.73% and 9.62 %; 9.25% and 8.65%; and 7.64 and 7.37%, respectively. Sand particles and phytoplankton have 6.07% and 6.73; and 4.64% and 6.73% by Frequency of occurrence and Numerical method respectively. Worm 4.17%, 3.31%; Insect 2.67%, 1.60%; Grain 2.29%, 0.96%; and Fluid 1.63%, 0.32% appeared to be incidental diets. In Mormyrus rume rume, Detritus constituted 30.07% and 30.48% of the content under frequency of occurrence and numerical method followed by Plant part with 21.03% and 21.90%. Phytoplankton, Worm, Insect, Mud and Insect part accounted for 14.09% and 14.76%; 7.84% and 7.14%; 7.52% and 7.14%; 7.38% and 7.14%; and 6.54% and 6.66 respectively. Sand particles, Fluid and Unidentified materials accounted for 3.79% and 3.33%; 1.33% and 0.95%; and 0.39% and 0.48% respectively in Frequency of occurrence and Numerical method as incidental diets. In Synodontis budgetti, Detritus constituted 31.45% and 31.93% of the content under frequency of occurrence and numerical method, followed by plant part with 21.68% and 22.69%. Insect part, Mud and Worm constituted 11.30% and 11.20%; 9.00% and 10.36%; and 5.36% and 5.04% respectively. Insect, Phytoplankton and Sand particles had 4.41% and 3.64%; 4.25% and 4.20%; and 4.24% and 4.48% in Frequency of occurrence and Numerical method respectively. Small fish, 2.65% and 1.40%; Snail, 1.78% and 1.12%; Grain, 1.61% and 1.68; Fluid, 1.28% and 1.12%; Shell, 0.86% and 0.84% and Unidentified material, 0.13% and 0.28% appeared as incidental diets in Frequency of occurrence and Numerical method respectively. Clarias gariepinus, Mormyrus rume rume and Synodondis budgetti exploit different varieties of food both of plant and animal origin. This ability makes these species to be Omnivorous in their feeding habit.